Becoming minority : how discourses and policies produce minorities in Europe and India - Tripathy, Jyotirmaya; Padmanabhan, Sudarsan (New Delhi : SAGE, 2016)
'Becoming Minority' traces the processes through which minorities perform as minorities, their discursive formation, narrativization and representation. The book moves away from an uncritical understanding of the term minority as a container of some unchanging core ideals, and leads to a framework where minority comes into existence in the very act of representation.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 25, 2016).
Keywords: Minorities -- Government policy -- India -- History; Minorities -- Government policy -- Europe -- History; Ethnicity -- Political aspects -- India -- History; Ethnicity -- Political aspects -- Europe -- History; Discourse analysis, Narrative -- Political aspects -- India -- History; Discourse analysis, Narrative -- Political aspects -- Europe -- History; India -- Ethnic relations -- History; Europe -- Ethnic relations -- History; India -- Social policy; Europe -- Social policy